2022
DOI: 10.35484/pssr.2022(6-ii)30
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Debt and Economic Growth Sustainability Nexus: An Empirical Analysis of Pakistan Economy

Abstract: This study is an attempt to make an assessment for the domestic debt and sustainable economic growth nexus for the Pakistan economy. In the absence of the forthcoming sustenance of the domestic debt, internal financial mobilization may prove to be a profligate strategy. This research investigates that either domestic debt has been a catalyst to foster the economic growth sustainability or otherwise. The time series data is considered spanning from 1990 to 2021. To obtain the empirical evidence of the research,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 4 publications
3
28
0
Order By: Relevance
“…Macroeconomic instability (M) and structural reform (B) are highly significant at the 1% level with the expected signs. The negative sign of the aggregate macroeconomic instability coefficient supports the argument that an economy with the desired degree of macroeconomic stability would provide incentives for the most productive destination of inputs and enhance the profitability of investments at reasonable rates of risk, which is consistent with the finding of Ali and Rehman (2015), Haghighi et al (2012) and Jannils (2021).…”
Section: Resultssupporting
confidence: 77%
“…Macroeconomic instability (M) and structural reform (B) are highly significant at the 1% level with the expected signs. The negative sign of the aggregate macroeconomic instability coefficient supports the argument that an economy with the desired degree of macroeconomic stability would provide incentives for the most productive destination of inputs and enhance the profitability of investments at reasonable rates of risk, which is consistent with the finding of Ali and Rehman (2015), Haghighi et al (2012) and Jannils (2021).…”
Section: Resultssupporting
confidence: 77%
“…Under this method, typical Granger causality tests for every panel is to be calculated and then estimates a Z bar statistic from the mediocre. Since there are many missing data in present dataset, this study employed the first method to inspect the Granger causality test as suggested by Ali and Rehman (2015). Arguing similar to Ali and Rehman (2015), author apply the Granger causality test approach assuming all cross-sections have the same coefficients and treating the panel an enormous arranged dataset.…”
Section: Empirical Results and Their Discussionmentioning
confidence: 99%
“…Authors stated that chronic macroeconomic volatility appears to be a significant barrier to public investment, particularly for its infrastructure component and thus hinders economic growth process. Analyzing panel data of 1980-2012, Ali and Rehman (2015) found a casual relation between macroeconomic instability and economic development. Authors argued that countries need to maintain their macroeconomic environment stable for achieving expected level of sustainable economic growth.…”
Section: Existing Empirical Studiesmentioning
confidence: 99%
“…Stability or fluctuations among macroeconomic indicators or variables have been found to play an influential role in the development of economies around the globe (refer to Bleaney, 1996; Sanchez-Robles, 1998; Haghighi et al ., 2012; Ali and Rehman, 2015; Liew et al ., 2018). The current study delves into the subject matter by assessing the impact of inflation uncertainty, macroeconomic risk and other key variables on financial institutions’ efficiency among SSA economies.…”
Section: Discussionmentioning
confidence: 99%